Social Security Reforms in Colombia : Striking Demographic and Fiscal Balances - Clavijo, Sergio (Washington, D.C. : International Monetary Fund, 2009)
This paper analyzes the economic rationale for adopting parametric pension reforms and reforms broadening the coverage of public health care in Colombia during 1993-2008. Parametric pension reforms have focused on increasing the retirement age and moderating replacement rates. The health system reforms aimed at reaching universal coverage by 2012, while providing a more homogenous level of services. Our results indicate that the Net Present Value of the debt of the social security system in Colombia is roughly 160 percent of GDP for pensions and about 97 percent of GDP for the health system.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet